Bilinguale Erziehung – neue Herausforderungen und Lösungen aus linguistischer Sicht - Utri, Reinhold (Wydawnictwo Naukowe UAM, 2009)
Bilingual education has many aspects. Teachers and parents of bilingual children face many difficult issues. This article starts with the definition of the problem and gives different types of bilingualism. Elements of the language programs in school, that are to be changed resp. developed, are presented. By this semilingualism should be avoided, the integration of children of a different L 1 and their equal career chances are to be guaranteed. Some innovative and creative projects show the right way.
New challenges and solutions from a linguistic point of view
Keywords: bilingualism; migrants; language of minorities; school; integration; bilingual instruction; language policy; status of language; drama